Thirteen novel ideas and underutilised resources to support progress towards a range‐wide American eel stock assessment - David K. Cairns; José Benchetrit; Louis Bernatchez; Virginie Bornarel; John M. Casselman; Martin Castonguay; Anthony R. Charsley; Malte Dorow; Hilaire Drouineau; Jens Frankowski; Alex Haro; Simon D. Hoyle; et al. (Fisheries Management and Ecology, 2022)
A robust assessment of the American eel ( Anguilla rostrata ) stock, required to guide conservation efforts, is challenged by the species’ vast range, high variability in demographic parameters and data inadequacies. Novel ideas and underutilised resources that may assist both analytic assessments and spatially oriented modelling include (1) species and environmental databases; (2) mining of data from scattered sources; (3) infilling of data gaps by spatial analysis; (4) age estimation from measurements of DNA methylation; evaluation of eel abundance by (5) larval, (6) glass‐bottom boat, (7) net enclosure and (8) eDNA surveys; (9) accounting for dam‐induced habitat increases in eel watercourse modelling; (10) spatially oriented modelling with and without temporal components; (11) geographically nested modelling of glass eel recruitment; (12) spawner per recruit modelling and (13) life cycle modelling to examine larval allocation effects. Eel biologists are too few to gather the required assessment data across all of the species’ range. Public posting of electrofishing and eDNA metabarcoding data sets and the use of machine learning techniques to comprehensively inventory small dams will help meet some data needs. These approaches address only a small proportion of the assessment challenges that face American eels. Worldwide collaboration amongst Anguilla scientists is a key enabler of progress towards stock assessment goals.